Judean Reception of the Elisha Narratives: An Alternative Reading of Elisha’s Promise to the Shunammite Woman (2 Kgs 4:8–17) from the Margins in Achaemenid Yehud - Skaria, Jobymon (Vetus Testamentum, 2025)
Scholars have noted scribal attempts to undermine Elisha’s prophetic reputation in his promise to the Shunammite woman (2 Kgs 4:8–17). However, these readings fail to adequately consider the intertextual links between Elisha’s promise and Yahweh’s promise to Abraham (Gen 18:1–15): Why did the scribes link Elisha’s promise with Yahweh’s promise, especially when the narrative is largely hostile against Elisha? Paying attention to the possible context in Achaemenid Yehud, this article proposes a new interpretation of Elisha’s promise: It highlights scribal efforts to subjugate and silence Bethel, a northern Israelite cultic site believed to be the repository for Elisha traditions during this period. And it argues that the Judean scribes deliberately linked Elisha’s promise with Yahweh’s promise, as an “antithetical parallelism” to support their attempts to stigmatise Bethel’s traditions by pointing readers toward Elisha’s human weaknesses and limitations in his prophetic career.